ANALYSIS OF URINE MICROALBUMIN LEVELS ON SERUM CREATININE IN PATIENTS WITH DIABETES MELLITUS IN THE CLINICAL LABORATORY OF MEDAN PRODIA - Ice Ratnalela Siregar; Yunilasari Hasibuan; Melika Ostina Purba (Poltekkes Kemenkes Medan, 2023)
Diabetes Mellitus is a degenerative disease that requires regular control. This disease occurs due to the pancreas not being able to produce enough insulin and/or when the body cannot produce insulin effectively so that it can cause various complications in the patient's organs. The purpose of this study was to determine the levels of Urine Microalbumin and Serum Creatinine at Prodia Clinical Laboratory Jl. Lt. Gen. S. Parman No. 17/223 G Medan. This research was conducted from August to October 2022 at the Clinical Laboratory of Prodia Medan. This type of research is descriptive Cross Sectional. This examination uses Immunoturbidimetric and Enzymatic Colorimetric methods with a total sample of 100 samples or the total of the population. The results of the research conducted showed that the number of Diabetes Mellitus patients at the Prodia Clinical Laboratory in Medan with gender as many as 48 men (48%) and 52 women (52%) samples. Normal Urine Microalbumin levels were 30 samples (30%) and High Urine Microalbumin levels were 70 samples (70%). Normal creatinine levels were 47 samples (47%) and abnormal creatinine levels were 53 samples (53%).